Организация и подготовка специалистов в области урановой геологии на кафедре геоэкологии и геохимии Томского политехнического университета - Язиков Егор Григорьевич; Рихванов Леонид Петрович (My University, 2016)
Приводится историческая справка и организация подготовки специалистов в области урановой геологии в настоящее время на базе кафедры геоэкологии и геохимии Томского политехнического университета. Рассматриваются основные моменты подготовки специалистов по магистерской программе с учетом лабораторной базы и учебно-методических материалов. The article deals with the background and current organization of training of specialists in uranium geology at the base of Geoecology and Geochemistry Department of Tomsk Polytechnic University. The basic principles of training for master students taking into account the laboratory facilities and educational learning materials are described in the paper.
Organization and training of specialists in uranium geology at the department of geoecology and geochemistry of Tomsk polytechnic university
Keywords: урановая геология; геоэкология; геохимия; ТПУ; магистерские программы